Mulheres escravizadas em ações de liberdade - Recife oitocentista - 1870-1885. - Harten, Maria Marinho (2020)
The text “Women enslaved in actions of freedom - Recife Oitocentista - 1870 - 1885” aims to build the narrative of the protagonism of enslaved women who sought the judicial arena as a strategy of resistance in the search for their rights and freedoms. The research started with freedom actions based on Law 2,040 of September 28, 1871. The purchase of manumission, customary law, then legalized, now has the possibility of mediation for tensions and conflicts with the landlord. The fragments and traces left in four arbitration actions by the enslaved women Rofina, Silvéria, Luiza and Benedicta were the guiding threads for unveiling the clashes that involved the slave agency and the movements around abolition in the port city scenario that “smelled of slavery” The research was based on the documentary collection of freedom actions stored in the Memorial of Justice of the State of Pernambuco, confronted with advertisements and news published in periodicals of the time, Diario de Pernambuco, Jornal do Recife and The Province-Organ of the Liberal Party and the recent historiography, allowing us to follow, nominally, real life characters, for the construction of a narrative beyond the space of judicialization, contemplating the transformations that left the city with abolitionist airs.